Metode Menghafal Al-Qur’an untuk Anak Tunalaras dengan Metode Fasih Al-Qur’an (Studi Kasus di Pondok Pesantren Ainul Yakin Yogyakarta) - Mahmud Rifaannudin; Syifa’ Nadia Rizka; Ahmad Fadly Rahman Akbar; Rezki Kaulan Maisurah (Universitas Darussalam Gontor, 2024)
A unique technique is needed for some people to memorize the Qur'an, especially children who struggle emotionally. Certain techniques designed for Qur'anic memorization are inapplicable to children with impairments. Therefore, understanding the Qur'an requires a unique approach, just as it does for children in general. Ainul Yakin Islamic Boarding School Yogyakarta gives children with disabilities a special method to be applied in memorizing the Qur'an called the